Subjective Video QoE with a Hybrid Cognitive-motor Task - Holub J.; Avetisyan H.; Lima P.-V. (IEEE, 2021)
This paper reports on the subjective video quality analysis with and without a parallel task. It aims to understand how the quality perceived by the human observer brain is affected when the subject is not entirely focused on the judgment task. For this purpose, two subjective video quality tests were performed according to the ITU-T P.910 recommendation - Subjective video quality assessment methods for multimedia applications. They consisted of two parts involving a total of 24 subjects. Unlike the first test, the second test included an additional (parallel) psychomotor task where subjects had to sort different colors of pasta into three bowls. Various analyses were provided, including preliminary analysis, group analysis, and RMSE analysis. Surprisingly, the results show that not all the spectrum of quality is affected equally by parallel task introduction.
Keywords: Video signal processing; Human Factors; Quality of Service